A construir la ciudad! - Domiinguez, Madelca; Scholastic Inc. (New York : Scholastic, 2011)
A new building is constructed in Lego City, and all different vehicles are used help build it, including an excavator, a bulldozer, and a crane.
Los camiones y las excavadoras no paran. Se esta construyendo un nuevo edificio!
Translation of: Build this city!
Text in Spanish.
Keywords: Building -- Juvenile fiction; LEGO toys -- Juvenile fiction; Building -- Fiction; LEGO toys -- Fiction; Spanish language materials; Construccion -- Novela juvenil; Juguetes -- Novela juvenil; Spanish language; Picture books for children